Experimental study of the TEMPO mediated copolymerization of styrene with divinylbenzene - Gonçalves, Miguel A.D. (2008)
Since the discovery of controlled radical polymerization (CRP) in the early nineties (Georges et al., 1993), an ever increasing activity has been focused on the production of polymers with narrow molecular weight distributions and well-de ned architectures (such as block copolymers, stars or brushes). This work describes an experimental research on the nitroxide-mediated radical polymerization (NMRP) of styrene (S) and divinylbenzenes (DVB) in xylene (X) solution at 130 °C, using the stable radical TEMPO (2,2,6,6-tetramethylpiperidinyl-1-oxy) as mediator and AIBN (azobisisobutyronitrile) as initiator. Measurements of absolute molecular weights and z-average radius of gyration of the produced copolymers have been performed for different polymerization times using a SEC system with coupled refractive index (RI) and multi-angle laser light scattering (MALLS) detectors.